PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ADOBE FLASH CS5 PADA TEMA 8 LINGKUNGAN SAHABAT KITA SUBTEMA 1 MANUSIA DAN LINGKUNGAN KELAS V SD NEGERI 104208 CINTA RAKYAT T.A 2019/2020 - Demu Karo-karo; Irsan Rangkuti; Putri Panca Wardhani (FIP Unimed, 2020)
The porpose of this study was to develop interactive learning media using Adobe Flash was appropriate for class V student SD Negeri 104208 Cinta Rakyat T.A 2019/2020. The type of research used is Research and Development with the ADDIE model through 4 stages, namely the Define, Design, Development, and Desseminate. The subject in the study were all studentsof class V SD Negeri 104208 Cinta Rakyat. The results of the study on aspects of media assessment got a score of 93 % with a very decent category.Keywords: Interactive Media, Adobe Flash